Marine Protected Area Networks in Indonesia: Progress, Lessons and a Network Design Case Study Covering Six Eastern Provinces. Issue 6 (2nd November 2021) - White, Alan; Rudyanto,; Agung, Muh Firdaus; Minarputri, Noorafebrianie; Lestari, Asri Puji; Wen, Wen; Fajariyanto, Yusuf; Green, Alison; Tighe, Stacey
Abstract: Indonesia is the largest archipelagic nation in the world with 17, 504 islands, a coastline of 108, 000 km and 15.8% (27, 255 km 2 ) of the world's coral reefs. This paper reviews the status of marine protected areas (MPAs) and networks of MPA in Indonesia, draws on lessons learned, and highlights what has been learned from the design of a network of MPAs for Fisheries Management Area (FMA) 715 across six eastern provinces as an example of how such work can be adapted for other parts of the country and elsewhere. Nationally, the 235, 622 km 2 of MPAs are mostly large (average 2, 380 km 2 ) with use zones and small no-take areas (<15 percent). MPAs are implemented by provincial governments or one of 2 national agencies. The design of a network of MPAs across FMA 715 began with 14 MPAs covering 1, 977, 276 ha or 4% of the marine waters of FMA 715 in 2016. Now there are 48 MPAs covering 3, 062, 206 hectares in the planning area, and the design process identified an additional 44 Areas of Interest required to establish new MPAs to augment the existing MPAs in FMA 715 to achieve the objectives of enhancing fisheries, protecting biodiversity, adapting to climate change while supporting community livelihoods and traditional practices. Issues identified in the process are that the scale and complexity of science and management needed is beyond what most stakeholders can easily comprehend; that implementation cuts across multiple jurisdictions with a still-new formal mandate for planning and managing the large network area; and, that the present process could only be possible with outside facilitating expertise. Finally, since the national conservation agency is currently finalizing legal guidelines for the planning and implementation of sub-national networks of MPA, this process has educated many and the result will lend legal and governance support to the continued planning and implementation of the FMA 715 MPA Network and for other areas.